Mix proportioning of artificial limestone bricks with waste glass powder - Turgut, Paki (My University, 2008)
The increased environmental awareness and increased cost for depositing waste have caused many construction companies to re-evaluate disposal wastes. A large amount of limestone powder wastes (LPW) are obtained in the quarrying operations of limestone and they are not used in the industries because of their fine nature. This paper presents a parametric experimental study which investigates the potential use of LPW and waste glass powder (WGP) for producing new low cost brick sample for the masonry units. The minimum cement amount for brick samples with LPW and LPW-WGP combinations, satisfying minimum compressive and flexural strength required in relevant international standards are found by making mix trials. The compressive strength and flexural strength, unit weight and water absorption values are obtained from the brick samples prepared and tested with the relevant international standards. The compressive strength and flexural strength and modulus of elasticity of brick samples with LPW-WGP combinations effectively are increased. Test results show that LPW and LPW-WGP combination provides results which are of potential to be used in producing economical new brick material for load-bearing masonry units.
Keywords: Brick; Cement; Limestone dust; Waste glass